# Theory Caratheodory

```(*  Title:      HOL/Analysis/Caratheodory.thy
Author:     Lawrence C Paulson
Author:     Johannes Hölzl, TU München
*)

section ‹Caratheodory Extension Theorem›

theory Caratheodory
imports Measure_Space
begin

text ‹
Originally from the Hurd/Coble measure theory development, translated by Lawrence Paulson.
›

lemma suminf_ennreal_2dimen:
fixes f:: "nat × nat ⇒ ennreal"
assumes "⋀m. g m = (∑n. f (m,n))"
shows "(∑i. f (prod_decode i)) = suminf g"
proof -
have g_def: "g = (λm. (∑n. f (m,n)))"
using assms by (simp add: fun_eq_iff)
have reindex: "⋀B. (∑x∈B. f (prod_decode x)) = sum f (prod_decode ` B)"
by (simp add: sum.reindex[OF inj_prod_decode] comp_def)
have "(SUP n. ∑i<n. f (prod_decode i)) = (SUP p ∈ UNIV × UNIV. ∑i<fst p. ∑n<snd p. f (i, n))"
proof (intro SUP_eq; clarsimp simp: sum.cartesian_product reindex)
fix n
let ?M = "λf. Suc (Max (f ` prod_decode ` {..<n}))"
{ fix a b x assume "x < n" and [symmetric]: "(a, b) = prod_decode x"
then have "a < ?M fst" "b < ?M snd"
by (auto intro!: Max_ge le_imp_less_Suc image_eqI) }
then have "sum f (prod_decode ` {..<n}) ≤ sum f ({..<?M fst} × {..<?M snd})"
by (auto intro!: sum_mono2)
then show "∃a b. sum f (prod_decode ` {..<n}) ≤ sum f ({..<a} × {..<b})" by auto
next
fix a b
let ?M = "prod_decode ` {..<Suc (Max (prod_encode ` ({..<a} × {..<b})))}"
{ fix a' b' assume "a' < a" "b' < b" then have "(a', b') ∈ ?M"
by (auto intro!: Max_ge le_imp_less_Suc image_eqI[where x="prod_encode (a', b')"]) }
then have "sum f ({..<a} × {..<b}) ≤ sum f ?M"
by (auto intro!: sum_mono2)
then show "∃n. sum f ({..<a} × {..<b}) ≤ sum f (prod_decode ` {..<n})"
by auto
qed
also have "… = (SUP p. ∑i<p. ∑n. f (i, n))"
unfolding suminf_sum[OF summableI, symmetric]
by (simp add: suminf_eq_SUP SUP_pair sum.swap[of _ "{..< fst _}"])
finally show ?thesis unfolding g_def
qed

subsection ‹Characterizations of Measures›

definition✐‹tag important› outer_measure_space where
"outer_measure_space M f ⟷ positive M f ∧ increasing M f ∧ countably_subadditive M f"

subsubsection✐‹tag important› ‹Lambda Systems›

definition✐‹tag important› lambda_system :: "'a set ⇒ 'a set set ⇒ ('a set ⇒ ennreal) ⇒ 'a set set"
where
"lambda_system Ω M f = {l ∈ M. ∀x ∈ M. f (l ∩ x) + f ((Ω - l) ∩ x) = f x}"

lemma (in algebra) lambda_system_eq:
"lambda_system Ω M f = {l ∈ M. ∀x ∈ M. f (x ∩ l) + f (x - l) = f x}"
proof -
have [simp]: "⋀l x. l ∈ M ⟹ x ∈ M ⟹ (Ω - l) ∩ x = x - l"
by (metis Int_Diff Int_absorb1 Int_commute sets_into_space)
show ?thesis
by (auto simp add: lambda_system_def) (metis Int_commute)+
qed

lemma (in algebra) lambda_system_empty: "positive M f ⟹ {} ∈ lambda_system Ω M f"
by (auto simp add: positive_def lambda_system_eq)

lemma lambda_system_sets: "x ∈ lambda_system Ω M f ⟹ x ∈ M"

lemma (in algebra) lambda_system_Compl:
fixes f:: "'a set ⇒ ennreal"
assumes x: "x ∈ lambda_system Ω M f"
shows "Ω - x ∈ lambda_system Ω M f"
proof -
have "x ⊆ Ω"
by (metis sets_into_space lambda_system_sets x)
hence "Ω - (Ω - x) = x"
by (metis double_diff equalityE)
with x show ?thesis
by (force simp add: lambda_system_def ac_simps)
qed

lemma (in algebra) lambda_system_Int:
fixes f:: "'a set ⇒ ennreal"
assumes xl: "x ∈ lambda_system Ω M f" and yl: "y ∈ lambda_system Ω M f"
shows "x ∩ y ∈ lambda_system Ω M f"
proof -
from xl yl show ?thesis
proof (auto simp add: positive_def lambda_system_eq Int)
fix u
assume x: "x ∈ M" and y: "y ∈ M" and u: "u ∈ M"
and fx: "∀z∈M. f (z ∩ x) + f (z - x) = f z"
and fy: "∀z∈M. f (z ∩ y) + f (z - y) = f z"
have "u - x ∩ y ∈ M"
by (metis Diff Diff_Int Un u x y)
moreover
have "(u - (x ∩ y)) ∩ y = u ∩ y - x" by blast
moreover
have "u - x ∩ y - y = u - y" by blast
ultimately
have ey: "f (u - x ∩ y) = f (u ∩ y - x) + f (u - y)" using fy
by force
have "f (u ∩ (x ∩ y)) + f (u - x ∩ y)
= (f (u ∩ (x ∩ y)) + f (u ∩ y - x)) + f (u - y)"
also have "... =  (f ((u ∩ y) ∩ x) + f (u ∩ y - x)) + f (u - y)"
also have "... = f (u ∩ y) + f (u - y)"
using fx [THEN bspec, of "u ∩ y"] Int y u
by force
also have "... = f u"
by (metis fy u)
finally show "f (u ∩ (x ∩ y)) + f (u - x ∩ y) = f u" .
qed
qed

lemma (in algebra) lambda_system_Un:
fixes f:: "'a set ⇒ ennreal"
assumes xl: "x ∈ lambda_system Ω M f" and yl: "y ∈ lambda_system Ω M f"
shows "x ∪ y ∈ lambda_system Ω M f"
proof -
have "(Ω - x) ∩ (Ω - y) ∈ M"
by (metis Diff_Un Un compl_sets lambda_system_sets xl yl)
moreover
have "x ∪ y = Ω - ((Ω - x) ∩ (Ω - y))"
by auto (metis subsetD lambda_system_sets sets_into_space xl yl)+
ultimately show ?thesis
by (metis lambda_system_Compl lambda_system_Int xl yl)
qed

lemma (in algebra) lambda_system_algebra:
"positive M f ⟹ algebra Ω (lambda_system Ω M f)"
apply (metis lambda_system_sets subsetD sets_into_space)
apply (metis lambda_system_empty)
apply (metis lambda_system_Compl)
apply (metis lambda_system_Un)
done

assumes z: "z ∈ M" and disj: "x ∩ y = {}"
and xl: "x ∈ lambda_system Ω M f" and yl: "y ∈ lambda_system Ω M f"
shows "f (z ∩ (x ∪ y)) = f (z ∩ x) + f (z ∩ y)"
proof -
have "z ∩ x = (z ∩ (x ∪ y)) ∩ x" using disj by blast
moreover
have "z ∩ y = (z ∩ (x ∪ y)) - x" using disj by blast
moreover
have "(z ∩ (x ∪ y)) ∈ M"
by (metis Int Un lambda_system_sets xl yl z)
ultimately show ?thesis using xl yl
qed

fix x and y
assume disj: "x ∩ y = {}"
and xl: "x ∈ lambda_system Ω M f" and yl: "y ∈ lambda_system Ω M f"
hence  "x ∈ M" "y ∈ M" by (blast intro: lambda_system_sets)+
thus "f (x ∪ y) = f x + f y"
using lambda_system_strong_additive [OF top disj xl yl]
qed

lemma lambda_system_increasing: "increasing M f ⟹ increasing (lambda_system Ω M f) f"

lemma lambda_system_positive: "positive M f ⟹ positive (lambda_system Ω M f) f"

lemma (in algebra) lambda_system_strong_sum:
fixes A:: "nat ⇒ 'a set" and f :: "'a set ⇒ ennreal"
assumes f: "positive M f" and a: "a ∈ M"
and A: "range A ⊆ lambda_system Ω M f"
and disj: "disjoint_family A"
shows  "(∑i = 0..<n. f (a ∩A i)) = f (a ∩ (⋃i∈{0..<n}. A i))"
proof (induct n)
case 0 show ?case using f by (simp add: positive_def)
next
case (Suc n)
have 2: "A n ∩ ⋃ (A ` {0..<n}) = {}" using disj
by (force simp add: disjoint_family_on_def neq_iff)
have 3: "A n ∈ lambda_system Ω M f" using A
by blast
interpret l: algebra Ω "lambda_system Ω M f"
using f by (rule lambda_system_algebra)
have 4: "⋃ (A ` {0..<n}) ∈ lambda_system Ω M f"
using A l.UNION_in_sets by simp
from Suc.hyps show ?case
qed

proposition (in sigma_algebra) lambda_system_caratheodory:
assumes oms: "outer_measure_space M f"
and A: "range A ⊆ lambda_system Ω M f"
and disj: "disjoint_family A"
shows  "(⋃i. A i) ∈ lambda_system Ω M f ∧ (∑i. f (A i)) = f (⋃i. A i)"
proof -
have pos: "positive M f" and inc: "increasing M f"
by (metis oms outer_measure_space_def)+
have A': "⋀S. A`S ⊆ (lambda_system Ω M f)" using A
by auto
interpret ls: algebra Ω "lambda_system Ω M f"
using pos by (rule lambda_system_algebra)
have A'': "range A ⊆ M"
by (metis A image_subset_iff lambda_system_sets)

have U_in: "(⋃i. A i) ∈ M"
by (metis A'' countable_UN)
have U_eq: "f (⋃i. A i) = (∑i. f (A i))"
proof (rule antisym)
show "f (⋃i. A i) ≤ (∑i. f (A i))"
using csa[unfolded countably_subadditive_def] A'' disj U_in by auto
have dis: "⋀N. disjoint_family_on A {..<N}" by (intro disjoint_family_on_mono[OF _ disj]) auto
show "(∑i. f (A i)) ≤ f (⋃i. A i)"
by (intro suminf_le_const[OF summableI]) (auto intro!: increasingD[OF inc] countable_UN)
qed
have "f (a ∩ (⋃i. A i)) + f (a - (⋃i. A i)) = f a"
if a [iff]: "a ∈ M" for a
proof (rule antisym)
have "range (λi. a ∩ A i) ⊆ M" using A''
by blast
moreover
have "disjoint_family (λi. a ∩ A i)" using disj
moreover
have "a ∩ (⋃i. A i) ∈ M"
by (metis Int U_in a)
ultimately
have "f (a ∩ (⋃i. A i)) ≤ (∑i. f (a ∩ A i))"
using csa[unfolded countably_subadditive_def, rule_format, of "(λi. a ∩ A i)"]
hence "f (a ∩ (⋃i. A i)) + f (a - (⋃i. A i)) ≤ (∑i. f (a ∩ A i)) + f (a - (⋃i. A i))"
also have "… ≤ f a"
fix n
have UNION_in: "(⋃i∈{0..<n}. A i) ∈ M"
by (metis A'' UNION_in_sets)
have le_fa: "f (⋃ (A ` {0..<n}) ∩ a) ≤ f a" using A''
by (blast intro: increasingD [OF inc] A'' UNION_in_sets)
have ls: "(⋃i∈{0..<n}. A i) ∈ lambda_system Ω M f"
using ls.UNION_in_sets by (simp add: A)
hence eq_fa: "f a = f (a ∩ (⋃i∈{0..<n}. A i)) + f (a - (⋃i∈{0..<n}. A i))"
have "f (a - (⋃i. A i)) ≤ f (a - (⋃i∈{0..<n}. A i))"
by (blast intro: increasingD [OF inc] UNION_in U_in)
thus "(∑i<n. f (a ∩ A i)) + f (a - (⋃i. A i)) ≤ f a"
qed
finally show "f (a ∩ (⋃i. A i)) + f (a - (⋃i. A i)) ≤ f a"
by simp
next
have "f a ≤ f (a ∩ (⋃i. A i) ∪ (a - (⋃i. A i)))"
by (blast intro:  increasingD [OF inc] U_in)
also have "... ≤  f (a ∩ (⋃i. A i)) + f (a - (⋃i. A i))"
by (blast intro: subadditiveD [OF sa] U_in)
finally show "f a ≤ f (a ∩ (⋃i. A i)) + f (a - (⋃i. A i))" .
qed
thus  ?thesis
by (simp add: lambda_system_eq sums_iff U_eq U_in)
qed

proposition (in sigma_algebra) caratheodory_lemma:
assumes oms: "outer_measure_space M f"
defines "L ≡ lambda_system Ω M f"
shows "measure_space Ω L f"
proof -
have pos: "positive M f"
by (metis oms outer_measure_space_def)
have alg: "algebra Ω L"
using lambda_system_algebra [of f, OF pos]
then
have "sigma_algebra Ω L"
using lambda_system_caratheodory [OF oms]
moreover
have "countably_additive L f" "positive L f"
using pos lambda_system_caratheodory [OF oms]
ultimately
show ?thesis
using pos by (simp add: measure_space_def)
qed

definition✐‹tag important› outer_measure :: "'a set set ⇒ ('a set ⇒ ennreal) ⇒ 'a set ⇒ ennreal" where
"outer_measure M f X =
(INF A∈{A. range A ⊆ M ∧ disjoint_family A ∧ X ⊆ (⋃i. A i)}. ∑i. f (A i))"

lemma (in ring_of_sets) outer_measure_agrees:
assumes posf: "positive M f" and ca: "countably_additive M f" and s: "s ∈ M"
shows "outer_measure M f s = f s"
unfolding outer_measure_def
proof (safe intro!: antisym INF_greatest)
fix A :: "nat ⇒ 'a set" assume A: "range A ⊆ M" and dA: "disjoint_family A" and sA: "s ⊆ (⋃x. A x)"
have inc: "increasing M f"
have "f s = f (⋃i. A i ∩ s)"
using sA by (auto simp: Int_absorb1)
also have "… = (∑i. f (A i ∩ s))"
using sA dA A s
by (intro ca[unfolded countably_additive_def, rule_format, symmetric])
(auto simp: Int_absorb1 disjoint_family_on_def)
also have "... ≤ (∑i. f (A i))"
using A s by (auto intro!: suminf_le increasingD[OF inc])
finally show "f s ≤ (∑i. f (A i))" .
next
have "(∑i. f (if i = 0 then s else {})) ≤ f s"
using positiveD1[OF posf] by (subst suminf_finite[of "{0}"]) auto
with s show "(INF A∈{A. range A ⊆ M ∧ disjoint_family A ∧ s ⊆ ⋃(A ` UNIV)}. ∑i. f (A i)) ≤ f s"
by (intro INF_lower2[of "λi. if i = 0 then s else {}"])
(auto simp: disjoint_family_on_def)
qed

lemma outer_measure_empty:
"positive M f ⟹ {} ∈ M ⟹ outer_measure M f {} = 0"
unfolding outer_measure_def
by (intro antisym INF_lower2[of  "λ_. {}"]) (auto simp: disjoint_family_on_def positive_def)

lemma (in ring_of_sets) positive_outer_measure:
assumes "positive M f" shows "positive (Pow Ω) (outer_measure M f)"
unfolding positive_def by (auto simp: assms outer_measure_empty)

lemma (in ring_of_sets) increasing_outer_measure: "increasing (Pow Ω) (outer_measure M f)"
by (force simp: increasing_def outer_measure_def intro!: INF_greatest intro: INF_lower)

lemma (in ring_of_sets) outer_measure_le:
assumes pos: "positive M f" and inc: "increasing M f" and A: "range A ⊆ M" and X: "X ⊆ (⋃i. A i)"
shows "outer_measure M f X ≤ (∑i. f (A i))"
unfolding outer_measure_def
proof (safe intro!: INF_lower2[of "disjointed A"] del: subsetI)
show dA: "range (disjointed A) ⊆ M"
by (auto intro!: A range_disjointed_sets)
have "∀n. f (disjointed A n) ≤ f (A n)"
by (metis increasingD [OF inc] UNIV_I dA image_subset_iff disjointed_subset A)
then show "(∑i. f (disjointed A i)) ≤ (∑i. f (A i))"
by (blast intro!: suminf_le)
qed (auto simp: X UN_disjointed_eq disjoint_family_disjointed)

lemma (in ring_of_sets) outer_measure_close:
"outer_measure M f X < e ⟹ ∃A. range A ⊆ M ∧ disjoint_family A ∧ X ⊆ (⋃i. A i) ∧ (∑i. f (A i)) < e"
unfolding outer_measure_def INF_less_iff by auto

assumes posf: "positive M f" and inc: "increasing M f"
shows "countably_subadditive (Pow Ω) (outer_measure M f)"
fix A :: "nat ⇒ _" assume A: "range A ⊆ Pow (Ω)" and sb: "(⋃i. A i) ⊆ Ω"
let ?O = "outer_measure M f"
show "?O (⋃i. A i) ≤ (∑n. ?O (A n))"
proof (rule ennreal_le_epsilon)
fix b and e :: real assume "0 < e" "(∑n. outer_measure M f (A n)) < top"
then have *: "⋀n. outer_measure M f (A n) < outer_measure M f (A n) + e * (1/2)^Suc n"
by (auto simp add: less_top dest!: ennreal_suminf_lessD)
obtain B
where B: "⋀n. range (B n) ⊆ M"
and sbB: "⋀n. A n ⊆ (⋃i. B n i)"
and Ble: "⋀n. (∑i. f (B n i)) ≤ ?O (A n) + e * (1/2)^(Suc n)"
by (metis less_imp_le outer_measure_close[OF *])

define C where "C = case_prod B o prod_decode"
from B have B_in_M: "⋀i j. B i j ∈ M"
by (rule range_subsetD)
then have C: "range C ⊆ M"
by (auto simp add: C_def split_def)
have A_C: "(⋃i. A i) ⊆ (⋃i. C i)"
using sbB by (auto simp add: C_def subset_eq) (metis prod.case prod_encode_inverse)

have "?O (⋃i. A i) ≤ ?O (⋃i. C i)"
using A_C A C by (intro increasing_outer_measure[THEN increasingD]) (auto dest!: sets_into_space)
also have "… ≤ (∑i. f (C i))"
using C by (intro outer_measure_le[OF posf inc]) auto
also have "… = (∑n. ∑i. f (B n i))"
using B_in_M unfolding C_def comp_def by (intro suminf_ennreal_2dimen) auto
also have "… ≤ (∑n. ?O (A n) + e * (1/2) ^ Suc n)"
using B_in_M by (intro suminf_le suminf_nonneg allI Ble) auto
also have "... = (∑n. ?O (A n)) + (∑n. ennreal e * ennreal ((1/2) ^ Suc n))"
using ‹0 < e› by (subst suminf_add[symmetric])
(auto simp del: ennreal_suminf_cmult simp add: ennreal_mult[symmetric])
also have "… = (∑n. ?O (A n)) + e"
unfolding ennreal_suminf_cmult
by (subst suminf_ennreal_eq[OF zero_le_power power_half_series]) auto
finally show "?O (⋃i. A i) ≤ (∑n. ?O (A n)) + e" .
qed
qed

lemma (in ring_of_sets) outer_measure_space_outer_measure:
"positive M f ⟹ increasing M f ⟹ outer_measure_space (Pow Ω) (outer_measure M f)"

lemma (in ring_of_sets) algebra_subset_lambda_system:
assumes posf: "positive M f" and inc: "increasing M f"
shows "M ⊆ lambda_system Ω (Pow Ω) (outer_measure M f)"
proof (auto dest: sets_into_space
fix x s assume x: "x ∈ M" and s: "s ⊆ Ω"
have [simp]: "⋀x. x ∈ M ⟹ s ∩ (Ω - x) = s - x" using s
by blast
have "outer_measure M f (s ∩ x) + outer_measure M f (s - x) ≤ outer_measure M f s"
unfolding outer_measure_def[of M f s]
proof (safe intro!: INF_greatest)
fix A :: "nat ⇒ 'a set" assume A: "disjoint_family A" "range A ⊆ M" "s ⊆ (⋃i. A i)"
have "outer_measure M f (s ∩ x) ≤ (∑i. f (A i ∩ x))"
unfolding outer_measure_def
proof (safe intro!: INF_lower2[of "λi. A i ∩ x"])
from A(1) show "disjoint_family (λi. A i ∩ x)"
by (rule disjoint_family_on_bisimulation) auto
qed (insert x A, auto)
moreover
have "outer_measure M f (s - x) ≤ (∑i. f (A i - x))"
unfolding outer_measure_def
proof (safe intro!: INF_lower2[of "λi. A i - x"])
from A(1) show "disjoint_family (λi. A i - x)"
by (rule disjoint_family_on_bisimulation) auto
qed (insert x A, auto)
ultimately have "outer_measure M f (s ∩ x) + outer_measure M f (s - x) ≤
(∑i. f (A i ∩ x)) + (∑i. f (A i - x))" by (rule add_mono)
also have "… = (∑i. f (A i ∩ x) + f (A i - x))"
using A(2) x posf by (subst suminf_add) (auto simp: positive_def)
also have "… = (∑i. f (A i))"
using A x
(auto intro!: arg_cong[where f=suminf] arg_cong[where f=f])
finally show "outer_measure M f (s ∩ x) + outer_measure M f (s - x) ≤ (∑i. f (A i))" .
qed
moreover
have "outer_measure M f s ≤ outer_measure M f (s ∩ x) + outer_measure M f (s - x)"
proof -
have "outer_measure M f s = outer_measure M f ((s ∩ x) ∪ (s - x))"
by (metis Un_Diff_Int Un_commute)
also have "... ≤ outer_measure M f (s ∩ x) + outer_measure M f (s - x)"
apply (simp add: positive_def outer_measure_empty[OF posf])
using s by (auto intro!: posf inc)
finally show ?thesis .
qed
ultimately
show "outer_measure M f (s ∩ x) + outer_measure M f (s - x) = outer_measure M f s"
by (rule order_antisym)
qed

lemma measure_down: "measure_space Ω N μ ⟹ sigma_algebra Ω M ⟹ M ⊆ N ⟹ measure_space Ω M μ"

subsection ‹Caratheodory's theorem›

theorem (in ring_of_sets) caratheodory':
assumes posf: "positive M f" and ca: "countably_additive M f"
shows "∃μ :: 'a set ⇒ ennreal. (∀s ∈ M. μ s = f s) ∧ measure_space Ω (sigma_sets Ω M) μ"
proof -
have inc: "increasing M f"
let ?O = "outer_measure M f"
define ls where "ls = lambda_system Ω (Pow Ω) ?O"
have mls: "measure_space Ω ls ?O"
using sigma_algebra.caratheodory_lemma
[OF sigma_algebra_Pow outer_measure_space_outer_measure [OF posf inc]]
hence sls: "sigma_algebra Ω ls"
have "M ⊆ ls"
hence sgs_sb: "sigma_sets (Ω) (M) ⊆ ls"
using sigma_algebra.sigma_sets_subset [OF sls, of "M"]
by simp
have "measure_space Ω (sigma_sets Ω M) ?O"
by (rule measure_down [OF mls], rule sigma_algebra_sigma_sets)
thus ?thesis using outer_measure_agrees [OF posf ca]
by (intro exI[of _ ?O]) auto
qed

lemma (in ring_of_sets) caratheodory_empty_continuous:
assumes f: "positive M f" "additive M f" and fin: "⋀A. A ∈ M ⟹ f A ≠ ∞"
assumes cont: "⋀A. range A ⊆ M ⟹ decseq A ⟹ (⋂i. A i) = {} ⟹ (λi. f (A i)) ⇢ 0"
shows "∃μ :: 'a set ⇒ ennreal. (∀s ∈ M. μ s = f s) ∧ measure_space Ω (sigma_sets Ω M) μ"
show "∀A∈M. f A ≠ ∞" using fin by auto
qed (rule cont)

subsection ‹Volumes›

definition✐‹tag important› volume :: "'a set set ⇒ ('a set ⇒ ennreal) ⇒ bool" where
"volume M f ⟷
(f {} = 0) ∧ (∀a∈M. 0 ≤ f a) ∧
(∀C⊆M. disjoint C ⟶ finite C ⟶ ⋃C ∈ M ⟶ f (⋃C) = (∑c∈C. f c))"

lemma volumeI:
assumes "f {} = 0"
assumes "⋀a. a ∈ M ⟹ 0 ≤ f a"
assumes "⋀C. C ⊆ M ⟹ disjoint C ⟹ finite C ⟹ ⋃C ∈ M ⟹ f (⋃C) = (∑c∈C. f c)"
shows "volume M f"
using assms by (auto simp: volume_def)

lemma volume_positive:
"volume M f ⟹ a ∈ M ⟹ 0 ≤ f a"
by (auto simp: volume_def)

lemma volume_empty:
"volume M f ⟹ f {} = 0"
by (auto simp: volume_def)

assumes "volume M f"
assumes A: "⋀i. i ∈ I ⟹ A i ∈ M" "disjoint_family_on A I" "finite I" "⋃(A ` I) ∈ M"
shows "f (⋃(A ` I)) = (∑i∈I. f (A i))"
proof -
have "A`I ⊆ M" "disjoint (A`I)" "finite (A`I)" "⋃(A`I) ∈ M"
using A by (auto simp: disjoint_family_on_disjoint_image)
with ‹volume M f› have "f (⋃(A`I)) = (∑a∈A`I. f a)"
unfolding volume_def by blast
also have "… = (∑i∈I. f (A i))"
proof (subst sum.reindex_nontrivial)
fix i j assume "i ∈ I" "j ∈ I" "i ≠ j" "A i = A j"
with ‹disjoint_family_on A I› have "A i = {}"
by (auto simp: disjoint_family_on_def)
then show "f (A i) = 0"
using volume_empty[OF ‹volume M f›] by simp
qed (auto intro: ‹finite I›)
finally show "f (⋃(A ` I)) = (∑i∈I. f (A i))"
by simp
qed

assumes pos: "⋀a. a ∈ M ⟹ 0 ≤ μ a"
assumes [simp]: "μ {} = 0"
assumes add: "⋀a b. a ∈ M ⟹ b ∈ M ⟹ a ∩ b = {} ⟹ μ (a ∪ b) = μ a + μ b"
shows "volume M μ"
proof (unfold volume_def, safe)
fix C assume "finite C" "C ⊆ M" "disjoint C"
then show "μ (⋃C) = sum μ C"
proof (induct C)
case (insert c C)
from insert(1,2,4,5) have "μ (⋃(insert c C)) = μ c + μ (⋃C)"
by (auto intro!: add simp: disjoint_def)
with insert show ?case
qed simp
qed fact+

proposition (in semiring_of_sets) extend_volume:
assumes "volume M μ"
shows "∃μ'. volume generated_ring μ' ∧ (∀a∈M. μ' a = μ a)"
proof -
let ?R = generated_ring
have "∀a∈?R. ∃m. ∃C⊆M. a = ⋃C ∧ finite C ∧ disjoint C ∧ m = (∑c∈C. μ c)"
by (auto simp: generated_ring_def)
from bchoice[OF this] obtain μ'
where μ'_spec: "∀x∈generated_ring. ∃C⊆M. x = ⋃ C ∧ finite C ∧ disjoint C ∧ μ' x = sum μ C"
by blast
{ fix C assume C: "C ⊆ M" "finite C" "disjoint C"
fix D assume D: "D ⊆ M" "finite D" "disjoint D"
assume "⋃C = ⋃D"
have "(∑d∈D. μ d) = (∑d∈D. ∑c∈C. μ (c ∩ d))"
proof (intro sum.cong refl)
fix d assume "d ∈ D"
have Un_eq_d: "(⋃c∈C. c ∩ d) = d"
using ‹d ∈ D› ‹⋃C = ⋃D› by auto
moreover have "μ (⋃c∈C. c ∩ d) = (∑c∈C. μ (c ∩ d))"
{ fix c assume "c ∈ C" then show "c ∩ d ∈ M"
using C D ‹d ∈ D› by auto }
show "(⋃a∈C. a ∩ d) ∈ M"
unfolding Un_eq_d using ‹d ∈ D› D by auto
show "disjoint_family_on (λa. a ∩ d) C"
using ‹disjoint C› by (auto simp: disjoint_family_on_def disjoint_def)
qed fact+
ultimately show "μ d = (∑c∈C. μ (c ∩ d))" by simp
qed }
note split_sum = this

{ fix C assume C: "C ⊆ M" "finite C" "disjoint C"
fix D assume D: "D ⊆ M" "finite D" "disjoint D"
assume "⋃C = ⋃D"
with split_sum[OF C D] split_sum[OF D C]
have "(∑d∈D. μ d) = (∑c∈C. μ c)"
by (simp, subst sum.swap, simp add: ac_simps) }
note sum_eq = this

{ fix C assume C: "C ⊆ M" "finite C" "disjoint C"
then have "⋃C ∈ ?R" by (auto simp: generated_ring_def)
with μ'_spec[THEN bspec, of "⋃C"]
obtain D where
D: "D ⊆ M" "finite D" "disjoint D" "⋃C = ⋃D" and "μ' (⋃C) = (∑d∈D. μ d)"
by auto
with sum_eq[OF C D] have "μ' (⋃C) = (∑c∈C. μ c)" by simp }
note μ' = this

show ?thesis
proof (intro exI conjI ring_of_sets.volume_additiveI[OF generating_ring] ballI)
fix a assume "a ∈ M" with μ'[of "{a}"] show "μ' a = μ a"
next
fix a assume "a ∈ ?R"
then obtain Ca where Ca: "finite Ca" "disjoint Ca" "Ca ⊆ M" "a = ⋃ Ca" ..
with μ'[of Ca] ‹volume M μ›[THEN volume_positive]
show "0 ≤ μ' a"
by (auto intro!: sum_nonneg)
next
show "μ' {} = 0" using μ'[of "{}"] by auto
next
fix a b assume "a ∈ ?R" "b ∈ ?R"
then obtain Ca Cb
where Ca: "finite Ca" "disjoint Ca" "Ca ⊆ M" "a = ⋃ Ca"
and Cb: "finite Cb" "disjoint Cb" "Cb ⊆ M" "b = ⋃ Cb"
by (meson generated_ringE)
assume "a ∩ b = {}"
with Ca Cb have "Ca ∩ Cb ⊆ {{}}" by auto
then have C_Int_cases: "Ca ∩ Cb = {{}} ∨ Ca ∩ Cb = {}" by auto

from ‹a ∩ b = {}› have "μ' (⋃(Ca ∪ Cb)) = (∑c∈Ca ∪ Cb. μ c)"
using Ca Cb by (intro μ') (auto intro!: disjoint_union)
also have "… = (∑c∈Ca ∪ Cb. μ c) + (∑c∈Ca ∩ Cb. μ c)"
using C_Int_cases volume_empty[OF ‹volume M μ›] by (elim disjE) simp_all
also have "… = (∑c∈Ca. μ c) + (∑c∈Cb. μ c)"
using Ca Cb by (simp add: sum.union_inter)
also have "… = μ' a + μ' b"
using Ca Cb by (simp add: μ')
finally show "μ' (a ∪ b) = μ' a + μ' b"
using Ca Cb by simp
qed
qed

subsubsection✐‹tag important› ‹Caratheodory on semirings›

theorem (in semiring_of_sets) caratheodory:
assumes pos: "positive M μ" and ca: "countably_additive M μ"
shows "∃μ' :: 'a set ⇒ ennreal. (∀s ∈ M. μ' s = μ s) ∧ measure_space Ω (sigma_sets Ω M) μ'"
proof -
have "volume M μ"
proof (rule volumeI)
{ fix a assume "a ∈ M" then show "0 ≤ μ a"
using pos unfolding positive_def by auto }
note p = this

fix C assume sets_C: "C ⊆ M" "⋃C ∈ M" and "disjoint C" "finite C"
have "∃F'. bij_betw F' {..<card C} C"
by (rule finite_same_card_bij[OF _ ‹finite C›]) auto
then obtain F' where "bij_betw F' {..<card C} C" ..
then have F': "C = F' ` {..< card C}" "inj_on F' {..< card C}"
by (auto simp: bij_betw_def)
{ fix i j assume *: "i < card C" "j < card C" "i ≠ j"
with F' have "F' i ∈ C" "F' j ∈ C" "F' i ≠ F' j"
unfolding inj_on_def by auto
with ‹disjoint C›[THEN disjointD]
have "F' i ∩ F' j = {}"
by auto }
note F'_disj = this
define F where "F i = (if i < card C then F' i else {})" for i
then have "disjoint_family F"
using F'_disj by (auto simp: disjoint_family_on_def)
moreover from F' have "(⋃i. F i) = ⋃C"
by (auto simp add: F_def split: if_split_asm cong del: SUP_cong)
moreover have sets_F: "⋀i. F i ∈ M"
using F' sets_C by (auto simp: F_def)
moreover note sets_C
ultimately have "μ (⋃C) = (∑i. μ (F i))"
using ca[unfolded countably_additive_def, THEN spec, of F] by auto
also have "… = (∑i<card C. μ (F' i))"
proof -
have "(λi. if i ∈ {..< card C} then μ (F' i) else 0) sums (∑i<card C. μ (F' i))"
by (rule sums_If_finite_set) auto
also have "(λi. if i ∈ {..< card C} then μ (F' i) else 0) = (λi. μ (F i))"
using pos by (auto simp: positive_def F_def)
finally show "(∑i. μ (F i)) = (∑i<card C. μ (F' i))"
qed
also have "… = (∑c∈C. μ c)"
using F'(2) by (subst (2) F') (simp add: sum.reindex)
finally show "μ (⋃C) = (∑c∈C. μ c)" .
next
show "μ {} = 0"
using ‹positive M μ› by (rule positiveD1)
qed
from extend_volume[OF this] obtain μ_r where
V: "volume generated_ring μ_r" "⋀a. a ∈ M ⟹ μ a = μ_r a"
by auto

interpret G: ring_of_sets Ω generated_ring
by (rule generating_ring)

have pos: "positive generated_ring μ_r"
using V unfolding positive_def by (auto simp: positive_def intro!: volume_positive volume_empty)

fix A' :: "nat ⇒ 'a set"
assume A': "range A' ⊆ generated_ring" "disjoint_family A'"
and Un_A: "(⋃i. A' i) ∈ generated_ring"

obtain C' where C': "finite C'" "disjoint C'" "C' ⊆ M" "⋃ (range A') = ⋃ C'"
using generated_ringE[OF Un_A] by auto

{ fix c assume "c ∈ C'"
moreover define A where [abs_def]: "A i = A' i ∩ c" for i
ultimately have A: "range A ⊆ generated_ring" "disjoint_family A"
and Un_A: "(⋃i. A i) ∈ generated_ring"
using A' C'
by (auto intro!: G.Int G.finite_Union intro: generated_ringI_Basic simp: disjoint_family_on_def)
from A C' ‹c ∈ C'› have UN_eq: "(⋃i. A i) = c"
by (auto simp: A_def)

have "∀i::nat. ∃f::nat ⇒ 'a set. μ_r (A i) = (∑j. μ_r (f j)) ∧ disjoint_family f ∧ ⋃(range f) = A i ∧ (∀j. f j ∈ M)"
(is "∀i. ?P i")
proof
fix i
from A have Ai: "A i ∈ generated_ring" by auto
from generated_ringE[OF this] obtain C
where C: "finite C" "disjoint C" "C ⊆ M" "A i = ⋃ C" by auto
have "∃F'. bij_betw F' {..<card C} C"
by (rule finite_same_card_bij[OF _ ‹finite C›]) auto
then obtain F where F: "bij_betw F {..<card C} C" ..
define f where [abs_def]: "f i = (if i < card C then F i else {})" for i
then have f: "bij_betw f {..< card C} C"
by (intro bij_betw_cong[THEN iffD1, OF _ F]) auto
with C have "∀j. f j ∈ M"
by (auto simp: Pi_iff f_def dest!: bij_betw_imp_funcset)
moreover
from f C have d_f: "disjoint_family_on f {..<card C}"
by (intro disjoint_image_disjoint_family_on) (auto simp: bij_betw_def)
then have "disjoint_family f"
by (auto simp: disjoint_family_on_def f_def)
moreover
have Ai_eq: "A i = (⋃x<card C. f x)"
using f C Ai unfolding bij_betw_def by auto
then have "⋃(range f) = A i"
using f by (auto simp add: f_def)
moreover
{ have "(∑j. μ_r (f j)) = (∑j. if j ∈ {..< card C} then μ_r (f j) else 0)"
using volume_empty[OF V(1)] by (auto intro!: arg_cong[where f=suminf] simp: f_def)
also have "… = (∑j<card C. μ_r (f j))"
by (rule sums_If_finite_set[THEN sums_unique, symmetric]) simp
also have "… = μ_r (A i)"
using C f[THEN bij_betw_imp_funcset] unfolding Ai_eq
by (intro volume_finite_additive[OF V(1) _ d_f, symmetric])
(auto simp: Pi_iff Ai_eq intro: generated_ringI_Basic)
finally have "μ_r (A i) = (∑j. μ_r (f j))" .. }
ultimately show "?P i"
by blast
qed
from choice[OF this] obtain f
where f: "∀x. μ_r (A x) = (∑j. μ_r (f x j)) ∧ disjoint_family (f x) ∧ ⋃ (range (f x)) = A x ∧ (∀j. f x j ∈ M)"
..
then have UN_f_eq: "(⋃i. case_prod f (prod_decode i)) = (⋃i. A i)"
unfolding UN_extend_simps surj_prod_decode by (auto simp: set_eq_iff)

have d: "disjoint_family (λi. case_prod f (prod_decode i))"
unfolding disjoint_family_on_def
proof (intro ballI impI)
fix m n :: nat assume "m ≠ n"
then have neq: "prod_decode m ≠ prod_decode n"
using inj_prod_decode[of UNIV] by (auto simp: inj_on_def)
show "case_prod f (prod_decode m) ∩ case_prod f (prod_decode n) = {}"
proof cases
assume "fst (prod_decode m) = fst (prod_decode n)"
then show ?thesis
using neq f by (fastforce simp: disjoint_family_on_def)
next
assume neq: "fst (prod_decode m) ≠ fst (prod_decode n)"
have "case_prod f (prod_decode m) ⊆ A (fst (prod_decode m))"
"case_prod f (prod_decode n) ⊆ A (fst (prod_decode n))"
using f[THEN spec, of "fst (prod_decode m)"]
using f[THEN spec, of "fst (prod_decode n)"]
by (auto simp: set_eq_iff)
with f A neq show ?thesis
by (fastforce simp: disjoint_family_on_def subset_eq set_eq_iff)
qed
qed
from f have "(∑n. μ_r (A n)) = (∑n. μ_r (case_prod f (prod_decode n)))"
by (intro suminf_ennreal_2dimen[symmetric] generated_ringI_Basic)
(auto split: prod.split)
also have "… = (∑n. μ (case_prod f (prod_decode n)))"
using f V(2) by (auto intro!: arg_cong[where f=suminf] split: prod.split)
also have "… = μ (⋃i. case_prod f (prod_decode i))"
using f ‹c ∈ C'› C'
(auto split: prod.split simp: UN_f_eq d UN_eq)
finally have "(∑n. μ_r (A' n ∩ c)) = μ c"
using UN_f_eq UN_eq by (simp add: A_def) }
note eq = this

have "(∑n. μ_r (A' n)) = (∑n. ∑c∈C'. μ_r (A' n ∩ c))"
using C' A'
(auto simp: disjoint_def disjoint_family_on_def
intro!: G.Int G.finite_Union arg_cong[where f="λX. suminf (λi. μ_r (X i))"] ext
intro: generated_ringI_Basic)
also have "… = (∑c∈C'. ∑n. μ_r (A' n ∩ c))"
using C' A'
by (intro suminf_sum G.Int G.finite_Union) (auto intro: generated_ringI_Basic)
also have "… = (∑c∈C'. μ_r c)"
using eq V C' by (auto intro!: sum.cong)
also have "… = μ_r (⋃C')"
using C' Un_A
(auto simp: disjoint_family_on_def disjoint_def
intro: generated_ringI_Basic)
finally show "(∑n. μ_r (A' n)) = μ_r (⋃i. A' i)"
using C' by simp
qed
obtain μ' where "(∀s∈generated_ring. μ' s = μ_r s) ∧ measure_space Ω (sigma_sets Ω generated_ring) μ'"
using G.caratheodory'[OF pos ‹countably_additive generated_ring μ_r›] by auto
with V show ?thesis
unfolding sigma_sets_generated_ring_eq
by (intro exI[of _ μ']) (auto intro: generated_ringI_Basic)
qed

lemma extend_measure_caratheodory:
fixes G :: "'i ⇒ 'a set"
assumes M: "M = extend_measure Ω I G μ"
assumes "i ∈ I"
assumes "semiring_of_sets Ω (G ` I)"
assumes empty: "⋀i. i ∈ I ⟹ G i = {} ⟹ μ i = 0"
assumes inj: "⋀i j. i ∈ I ⟹ j ∈ I ⟹ G i = G j ⟹ μ i = μ j"
assumes nonneg: "⋀i. i ∈ I ⟹ 0 ≤ μ i"
assumes add: "⋀A::nat ⇒ 'i. ⋀j. A ∈ UNIV → I ⟹ j ∈ I ⟹ disjoint_family (G ∘ A) ⟹
(⋃i. G (A i)) = G j ⟹ (∑n. μ (A n)) = μ j"
shows "emeasure M (G i) = μ i"

proof -
interpret semiring_of_sets Ω "G ` I"
by fact
have "∀g∈G`I. ∃i∈I. g = G i"
by auto
then obtain sel where sel: "⋀g. g ∈ G ` I ⟹ sel g ∈ I" "⋀g. g ∈ G ` I ⟹ G (sel g) = g"
by metis

have "∃μ'. (∀s∈G ` I. μ' s = μ (sel s)) ∧ measure_space Ω (sigma_sets Ω (G ` I)) μ'"
proof (rule caratheodory)
show "positive (G ` I) (λs. μ (sel s))"
by (auto simp: positive_def intro!: empty sel nonneg)
show "countably_additive (G ` I) (λs. μ (sel s))"
fix A :: "nat ⇒ 'a set" assume "range A ⊆ G ` I" "disjoint_family A" "(⋃i. A i) ∈ G ` I"
then show "(∑i. μ (sel (A i))) = μ (sel (⋃i. A i))"
by (intro add) (auto simp: sel image_subset_iff_funcset comp_def Pi_iff intro!: sel)
qed
qed
then obtain μ' where μ': "∀s∈G ` I. μ' s = μ (sel s)" "measure_space Ω (sigma_sets Ω (G ` I)) μ'"
by metis

show ?thesis
proof (rule emeasure_extend_measure[OF M])
{ fix i assume "i ∈ I" then show "μ' (G i) = μ i"
using μ' by (auto intro!: inj sel) }
show "G ` I ⊆ Pow Ω"
by (rule space_closed)
then show "positive (sets M) μ'" "countably_additive (sets M) μ'"
using μ' by (simp_all add: M sets_extend_measure measure_space_def)
qed fact
qed

proposition extend_measure_caratheodory_pair:
fixes G :: "'i ⇒ 'j ⇒ 'a set"
assumes M: "M = extend_measure Ω {(a, b). P a b} (λ(a, b). G a b) (λ(a, b). μ a b)"
assumes "P i j"
assumes semiring: "semiring_of_sets Ω {G a b | a b. P a b}"
assumes empty: "⋀i j. P i j ⟹ G i j = {} ⟹ μ i j = 0"
assumes inj: "⋀i j k l. P i j ⟹ P k l ⟹ G i j = G k l ⟹ μ i j = μ k l"
assumes nonneg: "⋀i j. P i j ⟹ 0 ≤ μ i j"
assumes add: "⋀A::nat ⇒ 'i. ⋀B::nat ⇒ 'j. ⋀j k.
(⋀n. P (A n) (B n)) ⟹ P j k ⟹ disjoint_family (λn. G (A n) (B n)) ⟹
(⋃i. G (A i) (B i)) = G j k ⟹ (∑n. μ (A n) (B n)) = μ j k"
shows "emeasure M (G i j) = μ i j"
proof -
have "emeasure M ((λ(a, b). G a b) (i, j)) = (λ(a, b). μ a b) (i, j)"
proof (rule extend_measure_caratheodory[OF M])
show "semiring_of_sets Ω ((λ(a, b). G a b) ` {(a, b). P a b})"
using semiring by (simp add: image_def conj_commute)
next
fix A :: "nat ⇒ ('i × 'j)" and j assume "A ∈ UNIV → {(a, b). P a b}" "j ∈ {(a, b). P a b}"
"disjoint_family ((λ(a, b). G a b) ∘ A)"
"(⋃i. case A i of (a, b) ⇒ G a b) = (case j of (a, b) ⇒ G a b)"
then show "(∑n. case A n of (a, b) ⇒ μ a b) = (case j of (a, b) ⇒ μ a b)"
using add[of "λi. fst (A i)" "λi. snd (A i)" "fst j" "snd j"]
by (simp add: split_beta' comp_def Pi_iff)
qed (auto split: prod.splits intro: assms)
then show ?thesis by simp
qed

end
```